The Role of Content Writing in Education: Theoretical Analysis through a Library Research Approach - Dayana, Yuliana Fatima; Fauziyah, Frisyi Fitriyani (Mitra Palupi, 2023)
Background: Advances in digital technology have brought significant changes to the world of education, especially in the way learning material is delivered. One emerging approach is to use content writing as a means to support a more interactive and effective learning process. However, there is a digital literacy gap in various educational institutions, especially in terms of mastering content writing techniques that suit the needs of students and the educational context. Research purposes: This research aims to explore concepts and roles of content writing in education, identifies the characteristics of effective content writing for learning, and provides a theoretical foundation for integrating content writing as a supporting tool in the learning process. Research Design: This research uses the method library research by collecting and analyzing various literature sources such as academic books, journal articles, and related case studies content writing and its implementation in education. Analysis was carried out to explore the concepts, principles, and application of relevant content writing strategies in formal and informal educational environments. Research result: The research results show that content writing Strategically designed ones have the potential to increase learning effectiveness through the delivery of information that is cohesive, interactive and interesting. Important characteristics include the use of simple but communicative language, a structure that facilitates understanding, and the integration of visual elements to support student attraction and engagement. This research also highlights the need for training for educators to master content writing skills as part of digital literacy. It is hoped that these findings can become the basis for developing learning-based strategies content writing which is more adaptive and innovative.